Evaluation of the Doktor Muda programme on the oral health of secondary school children in Kelantan / Siti Kamilah Mohamad Kasim - Siti Kamilah , Mohamad Kasim (2019)
Health Promoting School (HPS) concept is a strategy for health promotion by the WHO. In Malaysia, a similar concept was introduced in 1980s known as the Doktor Muda Programme (DMP) spearheaded by the Ministry of Health (MOH) and Ministry of Education (MOE). DMP was effective to promote oral health in primary schoolchildren. In 2015, DMP was introduced in secondary schools. However, no evaluation has been conducted on its impacts on oral health. Objectives: (i) to compare the impacts of DMP between schoolchildren attending DMP schools and schoolchildren attending non-DMP schools after 6 months in terms children’s oral health knowledge (OHK), oral health attitudes (OHA), oral health behaviours (OHB), oral health status (OHS) (oral hygiene, gingival health, caries incidence), and oral health-related quality of life (OHQRoL); (ii) to determine the associated factors for schoolchildren’s OHK, OHA, OHB, OHS, and OHRQoL; and (iii) to explore the process implementation of DMP in terms of Doktor Muda (DM) selection, training, DMP strengths and weaknesses, and suggestions for improvement from the perspectives of the DMs. Method: This study utilised a mixedmethod study design with 2 phases. Phase 1 was a quasi-experimental study involving Form 1 schoolchildren (12-13 years) in Kota Bharu and Pasir Mas Districts, Kelantan in 2018. The intervention group (IG) comprised DMP schools and the control group (CG) comprised non-DMP schools, matched by location. The sample size for the IG and CG was 270 and 265, respectively. Study tools included a validated questionnaire, O’Leary plaque index, the Gingival Index for Schoolchildren (GIS), the International Caries Detection and Assessment System (ICDAS), and the Malay Child Oral Impacts on Daily Performances (Malay Child-OIDP) index. Baseline data were collected prior to the DMP intervention, and again after 6 months. In Phase 2, focus group discussions (FGD) were conducted among DMs from the DMP schools. Quantitative data were analysed using SPSS software using descriptive, univariate and multivariate analyses. The qualitative data were transcribed verbatim and analysed using the framework method analysis. iv Results: The baseline and follow up response rate was 97.6% and 90.9%, respectively. There were no significant between-group differences in mean OHK and OHB increment scores after 6 months. However, the mean OHA increment score was significantly higher in the CG (p<0.001) after 6 months. Both groups had a significant decrement in mean plaque score after 6 months but no between-group difference was observed. The mean increment in score of GIS in the IG was significantly higher compared to the CG (p<0.001) after 6 months. A significantly lower proportion of schoolchildren in the IG experienced caries increment compared to schoolchildren in the CG after 6 months (p<0.05). In terms of OHRQoL, a lower proportion of schoolchildren in the IG experienced an increment in mean OIDP total score than schoolchildren in the CG after 6 months but no between-group difference in mean OIDP increment scores. The associated factors for OHK increment are gender and school location; for OHA increment are location, gender, type of school and OHK; for plaque score is school location; for GIS increment is type of school; for cavitated caries (tooth) is OHA increment; for cavitated surfaces are mother’s education level and OHA increment; for OIDP increment is OHK increment; and for at least 1 OIDP present are gender, mouth-rinsing behaviours, flossing frequency, and cavitated caries increment. From the FGDs, DMs perceived that their appointment was made by teachers, training was quite insufficient, with mixed feedback on support and materials provided. However, DMs perceived the programme improved their OHK and OHB including that of their peers. Recommendations for improvement included a dedicated health advisor, increase number of DMs, and longer time for DMP activities. Conclusion: The DMP in secondary school has some positive impacts on caries and OHRQoL after 6 months. Further improvements in DMP implementation are recommended to improve the effectiveness of DMP on schoolchildren’s oral health.